Against progress : intellectual property and fundamental values in the internet age - Silbey, Jessica (Stanford, California : Stanford University Press, 2022)
"When first written into the Constitution, intellectual property aimed to facilitate "progress of science and the useful arts" by granting rights to authors and inventors. The internet age has rendered more uncertain and fraught both the method of property rights and its purpose to promote knowledge and invention. Today, when rapid technological evolution accompanies growing wealth inequality and political and social divisiveness, the constitutional goal of "progress" may pertain to more basic, human values, redirecting IP's emphasis to the commonweal instead of private interests. Against Progress considers contemporary debates about intellectual property law as concerning the relationship between the constitutional mandate of progress and fundamental values, such as equality, privacy, and distributive justice, that are increasingly challenged in today's internet age. Following a legal analysis of various intellectual property court cases, Jessica Silbey examines the experiences of everyday creators and innovators navigating ownership, sharing, and self- and community sustainability within the internet eco-system and current IP laws. Their accounts expose intellectual property law as a framework through which to discuss essential socio-political issues. Crucially, the book encourages refiguring the substance of "progress" and the function of intellectual property in terms that demonstrate the urgency of art and science to social justice today"--
Introduction : is progress more? -- Everyone's a photographer now -- Equality -- Privacy -- Distributive justice (or fairer uses) -- Precarity and institutional failures.
Keywords: Propriedade intelectual -- Estados Unidos